The Collaboration of Stakeholders for Neighborhood Open Space Revitalization of Industrial Estate Community: The Case of Bang Plee New Town 1st Phase - Usavagovitwong, Nuttawut; Jongpukdee, Sukumaporn (Journal of Architectural/Planning Research and Studies (JARS), 2005)
This article is aimed at proposing the solutions to solve the problem of deteriorated recreational space within an industrial community. The solutions employ collaboration between stakeholders in order to achieve the best recreational space revitalization for communities both in an economic aspect and social aspect. The research team study communities located in Bangplee New Town, Samutprakarn Province- a new town with an industrial estate. The research process is divided into three steps. The first step is collection of data related to social and economic aspects of dwellers in order to assess their attitudes and needs. In this step, the researchers employ questionnaires survey and interviewing methods. In the second step, the researchers collect data of institutions who responsible for recreational space maintenance and development to assess their potential and limitation in terms of resources, authority and power. The research methods employ in this step are interviewing both at implementation level staffs and policyplanning level staffs. In the last step, the researchers analyze the structural relationship of the problems to propose the solutions. The research reveal that the most appropriate solutions is to build collaboration between stakeholders in different ways in order to enable each partner to take part in the revitalization process which finally entails a sustainable recreational space revitalization.